Archaic Votive Figurines from the Sanctuary of Demeter at Corinth - Susan Langdon (Les Carnets de l’ACoSt)
This work-in-progress focuses on the archaic figurines from the Corinthian sanctuary of Demeter and Kore on Acrocorinth. These include “Daedalic” plaques, handmade figurines with mold-made heads, fully handmade, and fully mold-made figures. The broadly varied assemblage documents the introduction of figurines into Corinthian votive practice and the development of cult iconography.